Understanding re-expatriation intentions among overseas returnees – an emerging economy perspective. Issue 17 (24th September 2016) - Ho, Nga Thi Thuy; Seet, Pi-Shen; Jones, Jane
Abstract : This study investigates the reasons why returnees in an emerging economy, Vietnam, who have studied and/or worked abroad, and who have returned to their home country, intend to re-expatriate on their own initiative. We combine pull–push theory with the theory of planned behaviour (TPB) to explain the re-expatriation intentions of returnees. Using path analysis on a sample of 290 Vietnamese returnees, we find three pull–push factors associated with home and host countries that have a significant impact on returnees' intention to re-expatriate: (1) dissatisfaction with career and life in their home country, (2) reverse culture shock and (3) expected career, family and quality-of-life outcomes from re-expatriation. For the TPB, we find that attitudes toward re-expatriation and subjective norms affect returnees' intention to re-expatriate. Further, these factors either fully or partially mediate the role of pull–push factors on intention to re-expatriate. The study adds to the limited number of empirical studies on self-initiated re-expatriation and brain circulation of returnees in emerging economies.